Emergencies in critical care - Beed, Martin; Sherman, Richard, Dr.; Mahajan, Ravi P. ([Oxford] : Oxford University Press, 2013)
A practical and accessible guide to the emergency situations which are commonly encountered in critical care, this title allows the reader to gain vital clinical information in an easy-to-follow format without spending much time scanning through superfluous detail.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 8, 2013).
Keywords: Critical care medicine; Emergency medicine